DAMPAK KESIAPAN ORGANISASI TERHADAP KEBERHASILAN CLOUD COMPUTING DI UMKM DENGAN MODEL DELONE DAN MCLEAN - Sani, Asrul; Andrianingsih, Andrianingsih; Aisyah, Siti; Taufik, Ahmad (ISTEK WIDURI, 2024)
This study investigates the critical success factors for cloud computing adoption in small and medium enterprises (SMEs) in Jabodetabek by integrating the DeLone and McLean information systems success model with organizational readiness. Through a quantitative survey approach, the research examines how system quality, information quality, and service quality influence organizational readiness and, subsequently, user satisfaction and net benefits of cloud computing. Results indicate that service quality has the strongest impact on organizational readiness, underscoring the importance of technical support in facilitating technological change. Furthermore, organizational readiness significantly enhances user satisfaction and operational benefits, emphasizing that well-prepared internal structures and skilled human resources are essential for successful cloud adoption. The study provides valuable insights for SME managers to strengthen organizational readiness, particularly in cultural and technical aspects, to optimize cloud computing outcomes. It also offers practical recommendations for policymakers to design training programs that enhance SMEs' technological capabilities. This research contributes to the literature by integrating quality and readiness perspectives, filling a gap in understanding how these factors jointly influence cloud adoption in SMEs. Future research could explore the long-term impacts of cloud adoption and validate these findings across different sectors and regions. ABSTRAKPenelitian ini mengkaji faktor-faktor keberhasilan kritis dalam adopsi cloud computing pada usaha mikro, kecil, dan menengah (UMKM) di wilayah Jabodetabek dengan mengintegrasikan model kesuksesan sistem informasi DeLone dan McLean serta kesiapan organisasi. Melalui pendekatan survei kuantitatif, penelitian ini menganalisis bagaimana kualitas sistem, kualitas informasi, dan kualitas layanan memengaruhi kesiapan organisasi dan selanjutnya kepuasan pengguna serta manfaat bersih dari cloud computing. Hasil penelitian menunjukkan bahwa kualitas layanan memiliki dampak terkuat pada kesiapan organisasi, menyoroti pentingnya dukungan teknis dalam memfasilitasi perubahan teknologi. Selain itu, kesiapan organisasi secara signifikan meningkatkan kepuasan pengguna dan manfaat operasional, menegaskan bahwa struktur internal yang siap dan sumber daya manusia yang terampil sangat penting untuk keberhasilan adopsi cloud. Studi ini memberikan wawasan praktis bagi manajer UMKM untuk memperkuat kesiapan organisasi, terutama dalam aspek budaya dan teknis, guna mengoptimalkan hasil adopsi cloud computing. Rekomendasi juga diberikan kepada pembuat kebijakan untuk merancang program pelatihan yang meningkatkan kapabilitas teknologi UMKM. Penelitian ini berkontribusi pada literatur dengan menggabungkan perspektif kualitas dan kesiapan, mengisi kesenjangan dalam memahami pengaruh bersama faktor-faktor ini terhadap adopsi cloud pada UMKM. Penelitian selanjutnya dapat mengeksplorasi dampak jangka panjang adopsi cloud dan memvalidasi temuan ini di sektor dan wilayah berbeda.